2014
DOI: 10.1371/journal.pntd.0003239
|View full text |Cite
|
Sign up to set email alerts
|

P. vivax Malaria and Dengue Fever Co-infection: A Cross-Sectional Study in the Brazilian Amazon

Abstract: BackgroundMalaria and dengue are the most prevalent vector-borne diseases worldwide and represent major public health problems. Both are endemic in tropical regions, propitiating co-infection. Only few co-infection cases have been reported around the world, with insufficient data so far to enhance the understanding of the effects of co-infection in the clinical presentation and severity.Methodology/Principal FindingsA cross-sectional study was conducted (2009 to 2011) in hospitalized patients with acute febril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 29 publications
10
74
6
1
Order By: Relevance
“…Nevertheless, there was a significant association between co-infection group and both mono-infection groups with hospitalized patients (p < 0.05). Almost Similar findings were seen in studies by Epelboin et al [11] and Magalhães et al [22], who found that the duration of fever was longer in co-infection patients and they were hospitalized more frequently than malaria and dengue monoinfection.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, there was a significant association between co-infection group and both mono-infection groups with hospitalized patients (p < 0.05). Almost Similar findings were seen in studies by Epelboin et al [11] and Magalhães et al [22], who found that the duration of fever was longer in co-infection patients and they were hospitalized more frequently than malaria and dengue monoinfection.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have described dual infections of Plasmodium and other arboviruses including DENV or CHIKV [2][3][4] . But co-infections with 3 different pathogens are rarely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although infection with Dengue or malaria can be life‐threatening, co‐infections with DENV and malaria could be more severe . Owing to the similar symptoms common to DENV‐ and malaria‐infected individuals, misdiagnosis of either, and/or co‐infections have informed the need for a differential diagnostic approach especially in DENV‐/malaria‐endemic regions . This study sought to investigate the incidence of co‐infections with DENV and malaria parasites in Ilorin, Nigeria, as well as the immunological status of febrile subjects against DENV infections in Ilorin, Nigeria.…”
Section: Introductionmentioning
confidence: 99%